Art and postcapitalism aesthetic labour, automation and value production - Beech, Dave (Pluto Press, 2019)
Artistic labour was exemplary for Utopian socialist theories of 'attractive labour', and Marxist theories of 'non alienated labour', but the rise of the anti-work movement and current theories of 'fully automated luxury communism' have seen art topple from its privileged place within the left's political imaginary as the artist has been reconceived as a prototype of the precarious 24/7 worker.